TERAPI KOMPLEMENTER TERHADAP PENURUNAN NYERI PADA PASIEN GASTRITIS: A LITERATUR REVIEW - Utami, Andinna Dwi; Kartika, Imelda Rahmayunia (Universitas Fort De Kock Bukittinggi, 2018)
Gastritis is inflammation that affects the gastric mucosa. This inflammation can cause swelling of the gastric mucosa until the release of the superficial mucosal epithelium is the most important cause of disorders in the digestive system. Pain is an unpleasant sensory and emotional experience due to actual and potential tissue damage. Pain Management using distraction, relaxation (Using deep breath) techniques, efflurage massage, guided imaginary, warm water compresses, progressive deep muscle relaxation techniques, hand held finger relaxation. The method used is used in review Literature review begins with the selection of topics, then the keyword is determined for searching journals using Indonesian and English through several databases including Google Scholar, Ebsco, and Pro Quest. This search is limited to journals from 2009 to 2019. Based on several explanations that have been stated, that the most commonly used complementary therapy is deep breath relaxation, because deep breath relaxation used for the therapeutic process greatly helps alleviate the pain experienced by patients because it facilitates the healing process and can be carried out independently by patients. Keywords: pain, gastritis patients, complementary therapy